Knowledge and practices about family planning among women attending the Obstetrics Outpatient Department of a newly established tertiary care center - Mohapatra, Ipsita; Samantaray, Subha R.; Soma, Hage; Pun, Shital K.; Halder, Barsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Birth spacing and appropriate family planning is the milestone for long term good health of both the mother and the child and in turn the betterment of the whole society. Before starting the Family Planning clinic, we wanted to have a thorough understanding of the levels of awareness and acceptance of various family planning methods among the women attending the outpatient department of this tertiary care hospital. This preliminary data would be helpful in planning suitable programs which would be helpful in enhancing the family planning acceptance and modifying the existing steps of approach. Methods: A cross-sectional descriptive study was done in the department of Obstetrics and Gynecology of the tertiary care hospital. The study group included 200 women within the reproductive (18-45 years) age group. Results: 88% of the participants were aware of some or the other methods of contraception. According to the participants, the main source of information was health care workers, friends, family members (mother and sisters) and various social platforms and television. 37% of women were not using any method despite being aware of contraceptive methods. Maximum women (65) were following coitus interruptus as a natural method of contraception.16.5% of women were using barrier method of contraception. Unawareness about contraceptive methods was the major reason behind not using any method of contraception. Though knowledge about contraception was reported by 88% of the study population, only 63% of them were actually using some method of contraception. Conclusions: The study shows that there is a gap between the level of awareness about various family planning services and the actual practice of any method of contraception by the study population. So, the main aim of starting of the family planning clinic at our institute would be to bridge this gap.